OPTIMIZATION OF THE OUTCOMES OF RECONSTRUCTIVE – RESTORATIVE OPERATIONS FOR COLON WITH REGARD TO THE PREVENTION PURULENT - SEPTIC COMPLICATIONS - Лихман В. М. (World of Medicine and Biology, 2015)
The results of surgical treatment of 107 patients undergoing reconstructive surgery after obstructive resection of the colon. Study group included 52 patients in the control group consisted of 55 patients. In the study, the main group of patients, antibiotic therapy was administered drugs including sensitivity to them microflora. Antibacterial drugs were administered intraoperatively and postoperatively in endolymphatic catheterized inguinal lymph node.